2015
DOI: 10.1021/jf505014n
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Antioxidant Activity of Polyphenol- and Isothiocyanate-Enriched Fractions fromMoringa oleifera

Abstract: Moringa oleifera Lam. is a fast-growing, tropical tree with various edible parts used as nutritious food and traditional medicine. This study describes an efficient preparatory strategy to extract and fractionate moringa leaves by fast centrifugal partition chromatography (FCPC) to produce polyphenol and isothiocyanate (ITC) rich fractions. Characterization and further purification of these fractions showed that moringa polyphenols were potent direct antioxidants assayed by oxygen radical absorbance capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 43 publications
2
71
1
4
Order By: Relevance
“…In our study, dietary MOL decreased serum MDA. Previous studies demonstrated that the MOL possessed potent antioxidant properties due to its high contents of phenolic compounds and isothiocyanate (Tumer, Rojas-Silva, Poulev, Raskin, & Waterman, 2015;Verma et al, 2009). Additionally, Moringa oleifera leaf and fruit extracts were found to reduce MDA levels both in vitro and in vivo (Luqman, Srivastava, Kumar, KumarMaurya, & Chanda, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, dietary MOL decreased serum MDA. Previous studies demonstrated that the MOL possessed potent antioxidant properties due to its high contents of phenolic compounds and isothiocyanate (Tumer, Rojas-Silva, Poulev, Raskin, & Waterman, 2015;Verma et al, 2009). Additionally, Moringa oleifera leaf and fruit extracts were found to reduce MDA levels both in vitro and in vivo (Luqman, Srivastava, Kumar, KumarMaurya, & Chanda, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Either the direct action of antioxidants which are usually small molecules that directly clean up reactive oxygen species (ROS) or nitrogen species, or the indirect action of antioxidants which acts through the activation of phase II metabolic enzymes (such as glutathione S-transferase, aldehide reductase etc.) (Dinkova-Kostova and Talalay 2008;Tumer et al 2015). Thus, glucosinolates and isothiocyanates are considered as indirect antioxidants, because they trigger the transcription of phase II metabolic enzymes (Ishida et al 2014;Vig et al 2009;Cartea González et al 2008;Fuentes et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf powder capsules (4 g) considerably improved the discharge of insulin in 10 healthy human volunteers (Anthanont, Lumlerdkij, Akarasereenont, Vannasaeng, & Sriwijitkamol, ). 4‐[(α‐ l ‐rhamnosyloxy)benzyl] isothiocyanate and 4‐[(4′‐O‐acetyl‐α‐ l ‐rhamnosyloxy)benzyl] isothiocyanate showed antidiabetic activity (Tumer et al, ; Waterman et al, ). In alloxan‐induced diabetic rats, the aqueous extract (300 mg/kg) exhibited 44.06% reduction respectively of blood glucose concentration within 6 hr of administration, whereas almost as effective as the standard drug tolbutamide (200 mg/kg,) caused 46.75% reduction (Edoga, Njoku, Amadi, & Okeke, ).…”
Section: Resultsmentioning
confidence: 99%
“…MO tree contains about 40 natural antioxidants (Mahmood et al, ). The antioxidant activity is attributed due to the presence of various types of antioxidant compounds (Omodanisi et al, ; Siddhuraju & Becker, ) such as ascorbic acid, β‐carotene (Kumar, Pandey, Mohan, & Singh, ; Mahajan & Mehta, ), quercetin, kaempferol (Gupta et al, ), flavonoids, phenolics (Anwar, Ashraf, & Bhanger, ; Sreelatha et al, ), isothiocyanates, polyphenols, and rutin in leaves (Tumer et al, ); myricetin (Lalas & Tsaknis, ), tocopherols and lectins in seeds (Singh et al, ); procyanidins in stem and root bark (Atawodi et al, ) and palmitic acid, phytosterols, and 9‐octadecenamide in flowers (Inbathamizh & Padmini, ), monopalmitic acid, oleic acid, tri‐oleic triglycerides in seed oil (Lalas & Tsaknis, ; Mahajan & Mehta, ). Methanol and acetone extracts of leaves (Atawodi et al, ; Charoensin, ), aqueous extracts of roots (Satish, Kumar, Rakshith, Satish, & Ahmed, ), methanolic extracts of stem and pods (Gupta et al, ; Kumbhare, Guleha, & Sivakumar, ) showed wide antioxidant profile.…”
Section: Resultsmentioning
confidence: 99%